THE KINSHIP SYSTEM OF KLUET ETNICS IN SOUTH ACEH - Essi Hermaliza (Pusbindiklat - LIPI, 2011)
This research was conducted to analyze and inventoried form of the kinship system of Kluet etnics in South Aceh focused on Kluet’s society who lived in Kluet Timur subdistrict. To get the accurate data dealing with the research problem, the researcher used depth interview approach supported by observation technique. It was found that some actual data inferred that Kluet is unique, particularly in kinship system. They hold patrilineal kinship system appearing in applying Marga at the end of their name and the main family, also applying matrilineal kinship system appearing from the larger family and customary events. Kinship system which is a part of local culture is needed to be preserved as a local cultural heritage; it is inside of the society.